VEGF expression and new blood vessel after dental X-ray irradiation on fractured tooth extraction wound - Niluh Ringga Woroprobosari; Jenny Sunariani; Eha Renwi Astuti (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background:Dental X-ray has an important role in dentistry. Complication case such as tooth fracture extraction requires this examination to determine the appropriate treatment measures. Dental X-ray can also cause a negative impact to the body at cellular and even molecular level. Purpose: The aim of this study was to evaluate the decrease of vascular endothelial growth factor (VEGF) expression and new blood vessels number caused by dental X-ray irradiation on fractured tooth extraction wound on day 3 and 7 after extraction. Method: We used 30 wistar rats which was randomly divided into 6 groups. Each rat’s central insisive of left mandible was fractured and then extracted after or without X-ray irradiation. Group KA and KB were control groups without irradiation. Group P1 A and P1 B were treatment groups with 0.08 mSv irradiation dose. Group P2 A and P2 B were treatment groups with 0.16 mSv irradiation dose. The subject from group KA, P1 A, and P2 A were sacrficed and sockets were collected at day 3. The subject from group KB, P1 B, and P2 B were sacrficed and sockets were collected at day 7. Socket were processed and painted with hematoxylin eosin and immunohistochemistry, then observed with a microscope. Data processing was performed with SPSS 16 through one way anova test and post hoc Tukey test HS. Result: The lowest means expression of VEGF and the number of new blood vessels on the day 3 was found in P2 A group, and the highest found in the KA group. The lowest means expression of VEGF and the number of new blood vessels on the day 7 was found in P2 B group, and the highest found in the KB group. Conclusion: Dental X-ray irradiation dose of 0.08 mSv and 0.16 mSv causes decrease of VEGF expression and new blood vessels in the wound fractured tooth extraction in day 3 and day 7 post-extraction.